Mathematical modelling of diffusion in physico-chemical systems - Murphy, Judith (Trinity College (Dublin, Ireland). School of Chemistry, 2000)
The purpose of this thesis was to investigate the usefulness of mathematical modelling as an aid to understanding the physico chemical processes of iontophoresis in transdermal drug delivery and electrochemical sensor technology. We begin by presenting a general introduction to mathematical modelling. In chapter one we show how it was used in the early stages of mathematics and how it has developed as a powerful tool for an industrial, economic and social disciplines of the modern world. From this we discuss one of our physical systems, paying particular attention to the complexity of the system and the difficulties associated with modelling this.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin